Are all erythropoiesis-stimulating agents created equal?. Issue 8 (24th March 2020) - Locatelli, Francesco; Del Vecchio, Lucia; De Nicola, Luca; Minutolo, Roberto
Abstract: Erythropoiesis-stimulating agents (ESAs) are effective drugs to correct and maintain haemoglobin (Hb) levels, however, their use at doses to reach high Hb targets has been associated with an increased risk of cardiovascular adverse events, mortality and cancer. Presently used ESAs have a common mechanism of action but different pharmacokinetic and pharmacodynamic characteristics. Accordingly, the mode of activation of the erythropoietin (EPO) receptor can exert marked differences in downstream events. It is unknown whether the various ESA molecules have different efficacy/safety profiles. The relative mortality and morbidity risks associated with the use of different types of ESAs remains poorly evaluated. Recently an observational study and a randomized clinical trial provided conflicting results regarding this matter. However, these two studies displayed several differences in patient characteristics and ESA molecules used. More importantly, by definition, randomized clinical trials avoid bias by indication and suffer less from confounding factors. Therefore they bring a higher degree of evidence. The scenario becomes even more complex when considering the new class of ESAs, called prolyl-hydroxylase domain (PHD) inhibitors. They are oral drugs that mimic exposure to hypoxia and stabilize hypoxia-inducible factor α. They profoundly differ from presently used ESAs, as they have multiple targets of action, including the stimulation of endogenous EPO synthesis, direct mobilization/absorption of iron and a higher reduction of hepcidin. Accordingly, they have the potential to be more effective in inflamed patients with functional iron deficiency, i.e. the setting of patients who are at higher risk of cardiovascular events and mortality in response to present ESA use. As for ESAs, individual PHD inhibitors differ in molecular structure and degree of selectivity for the three main PHD isoforms; their efficacy and safety profiles may therefore be different from that of presently available ESAs.